Faktor Kriminogen Implementasi Program Bantuan Pangan Non Tunai - Rizqi Robi Ali Sodiqina (Universitas Palangka Raya, 2024)
The Non-Cash Food Assistance Program (BPNT), there are indications of program deviation from the program benefit indicators. This paper aims first, to analyze the criminogenic factors that cause deviations from the BPNT program. Second, analyze how actors with an interest in contributing to deviations from the BPNT program work. This research is normative juridical in nature. Analysis orientation through legal and conceptual approaches. The research findings explain that first, the source of criminogens comes from internal program organizers, namely the accompanying team and the Social Service. The external aspect comes from non-governmental actors who have an interest in becoming monopoly suppliers of food. Second, the modus operandi used is through packaging certain food ingredients, resulting in financial losses to the State and a reduction in benefits that should be received by Beneficiary Families (KPM).